Local Ancestry and Selection in the Genomes of Russian Black Pied Cattle - Alexander V. Igoshin; Andrey A. Yurchenko; Nikolay S. Yudin; Denis M. Larkin (Sci)
The Russian Black Pied (RBP) is one of Russia’s most popular dairy cattle breeds. It was developed in the USSR during the 1930s by crossing Russian native cattle with Dutch cattle. Since the mid-1970s, the RBP has been cross-bred with Holstein cattle to enhance milk production. To trace haplotypes and selection signatures in the RBP genomes formed during cross-breeding and selection, we conducted local ancestry inference and scans for selection signatures in 12 resequenced RBP animals. Scans for selection using hapFLK and window-based FST identified 65 putatively selected regions across the genome, with 4 identified by both methods. Candidate missense variants were detected within these regions, including KIAA1755, CNBD1, and MPZL3, which may be related to milk traits, pathogen resistance, and climate adaptation. Local ancestry inference and functional annotation analyses suggest that regions with a higher fraction of native haplotypes are enriched for genes associated with keratin filaments, antimicrobial defence, the immune system, protein digestion, and amino acid transporters. The results of our study could be utilised for conservation purposes and the improvement of this and other breeds.